The objectives of the new international economic order - Laszlo, Ervin, 1932- (Pergamon policy studies., 1978)
The Objectives of the New International Economic Order focuses on the role of the New International Economic Order (NIEO) in the resolution of issues in world economy, international trade, economic policies, trade relations, and business practices. The manuscript first offers information on the objectives of the NIEO in historical and global perspectives, as well as the political relevance of the NIEO, historical factors in the emergence of the NIEO, and contrary perceptions and vicious circles. The book also takes a look at the objectives of the NIEO regarding issues in world economy. Concern.